Critical Factors of E-Learning Adoption and Acceptance in Pakistan: A Literature Review - Kanwal, F.; Rehman, M.; Bashir, K.; Qureshi, U. (Engineering, Technology & Applied Science Research, 2017)
This review paper examines the prior studies on critical factors of e-learning adoption in Pakistan. The search terms identified 40 papers reporting 25 conceptual and qualitative and 15 quantitative evidence about the e-learning adoption and critical factors that may influence the adoption of e-learning in Pakistan. The findings revealed that modern paradigm shift requires the in-depth analysis of government policies, institutional and management role, students and faculty attitude, social norms, cultural values as well as technological advancement. These factors may directly or indirectly affect the intention of students towards e-learning adoption. The lack of quantitative evidences illustrate that policy makers, practitioners and researchers need to pay attention for further research of identifying and analyzing the critical factors which enhances the e-learning adoption in Pakistan.